Privatised enforcement and the right to freedom of expression in a world confronted with terrorism propaganda online - Eugénie Coche (Internet Policy Review, 2018)
The purpose of this paper is to explore the risks of privatised enforcement in the field of terrorism propaganda, stemming from the EU Code of conduct on countering illegal hate speech online. By shedding light on this Code, the author argues that implementation of it may undermine the rule of law and give rise to private censorship. In order to outweigh these risks, IT companies should improve their transparency, especially towards users whose content have been affected. Where automated means are used, the companies should always have in place some form of human intervention in order to contextualise posts. At the EU level, the Commission should provide IT companies with clearer guidelines regarding their liability exemption under the e-Commerce Directive. This would help prevent a race-to-the bottom where intermediaries choose to interpret and apply the most stringent national laws in order to secure at utmost their liability. The paper further articulates on the fine line that exists between 'terrorist content' and 'illegal hate speech' and the need for more detailed definitions.
Keywords: 300; Code of conduct on countering illegal hate speech online; Privatised enforcement; Illegal hate speech; Terrorism propaganda; Freedom of expression